Black Religion and Aesthetics - Pinn, A. author. aut Link
XI, 220 p.
Keywords: A great deal of attention has been given to the sociopolitical and theological importance of Black Religion. However, of less academic concern up to this point is the aesthetic qualities that define much of what is said and done within the context of Black Religion. Recognizing the centrality of the black body for black religious thought and life, this book proposes a conversation concerning various dimensions of the aesthetic considerations and qualities of Black Religion as found in various parts of the world, including the the Americas, the Caribbean, Africa, and Europe. In this respect, Black Religion is simply meant to connote the religious orientations and arrangements of people of African descent across the globe.